188. Sustainability of Antibiotic Stewardship Programs: Perceptions & Experiences of Nursing Home Staff. (31st December 2020) - Seshadri, Sandhya; Felsen, Christina B; Sellers, Craig R; Dumyati, Ghinwa
Abstract: Background: A hospital-based team (HBT) with antibiotic stewardship (AS) expertise provided knowledge, education, and training on AS to successfully implement antibiotic stewardship programs (ASPs) in 9 nursing homes (NHs). However, as integrating AS efforts into NH operations was challenging, we sought to understand the factors that influence ASP sustainability in NHs without the support of the HBT. Methods: Using a qualitative descriptive design, we conducted 48 semi-structured interviews with clinical and administrative staff across the NHs. Interview data were de-identified and transcribed verbatim. Utilizing an integrated sustainability framework (Shelton, Cooper, & Stirman, 2018), a codebook (see Figure 1 for categories and codes) was developed to systematically code and analyze the data. Figure 1 Categories & Codes Results: Seven themes were identified (Figure 2): (1) An ASP is resource intensive for NHs with limited resources; (2) No matter how committed, a single person cannot sustain an ASP; (3) An ASP requires access to and interpretation of data not readily available at many NHs; (4) ASP sustainability requires external partnership, internal leadership support, and collaboration across longstanding disciplinary boundaries; (5) It is hard to "get to step two" and sustain an ASP because clinical "fires come first"; (6) Consistent and constant education on AS is important for sustainability; and (7) Outer contextual factors impede stewardship efforts. An ASP was perceived as complex requiring resources beyond what was available in most NHs. Lack of funding, electronic health records, and adequate staff to care for residents with complex medical needs influenced the ability of ASP leads to build and sustain the program. External providers, residents' families, and regulators influenced antibiotic prescribing patterns, while consistent education and training, leadership buy-in, and collaborations were perceived as vital for long-term success. Figure 2 Sustainability of ASPs in Nursing Homes: Themes Conclusion: Multiple interconnected factors impact ASP sustainability. We recommend that NHs prioritize and focus on three critical areas: (1) providing explicit leadership support, (2) maintaining partnerships with an AS expert and fostering internal inter-professional collaborations, and (3) providing consistent education and training for all staff . Disclosures: Ghinwa Dumyati, MD, Roche Diagnostics (Consultant)